Mitochondrial metabolism and hypoxic signaling in differentiated human cardiomyocyte AC16 cell line - Alan, Lukas; Opletalova, Barbora; Hayat, Habiba; Markovic, Aleksandra; Hlavackova, Marketa; Vrbacky, Marek; Mracek, Tomas; Alanova, Petra (American journal of physiology. Cell physiology, 2025)
Cardiovascular diseases are associated with an altered cardiomyocyte metabolism. Because of a shortage of human heart tissue, experimental studies mostly rely on alternative approaches including animal and cell culture models. Since the use of isolated primary cardiomyocytes is limited, immortalized cardiomyocyte cell lines may represent a useful tool as they closely mimic human cardiomyocytes. This study is focused on the AC16 cell line generated from adult human ventricular cardiomyocytes. Despite an increasing number of studies employing AC16 cells, a comprehensive proteomic, bioenergetic, and oxygen-sensing characterization of proliferating vs. differentiated cells is still lacking. Here, we provide a comparison of these two stages, particularly emphasizing cell metabolism, mitochondrial function, and hypoxic signaling. Label-free quantitative mass spectrometry revealed a decrease in autophagy and cytoplasmic translation in differentiated AC16, confirming their phenotype. Cell differentiation led to global increase in mitochondrial proteins [e.g. oxidative phosphorylation (OXPHOS) proteins, TFAM, VWA8] reflected by elevated mitochondrial respiration. Fatty acid oxidation proteins were increased in differentiated cells, whereas the expression levels of proteins associated with fatty acid synthesis were unchanged and glycolytic proteins were decreased. There was a profound difference between proliferating and differentiated cells in their response to hypoxia and anoxia-reoxygenation. We conclude that AC16 differentiation leads to proteomic and metabolic shifts and altered cell response to oxygen deprivation. This underscores the requirement for proper selection of the particular differentiation state during experimental planning.NEW & NOTEWORTHY Proliferating and differentiated AC16 cell lines exhibit distinct proteomic and metabolic profiles with critical implications for experimental design. Proliferating cells predominantly utilize glycolysis and are highly sensitive to hypoxia, whereas differentiated cells display enhanced mitochondrial biogenesis, oxidative phosphorylation, and resistance to anoxia-reoxygenation. These findings provide novel insights into the metabolic adaptations during differentiation and highlight the necessity of selecting the appropriate cellular stage to ensure accurate experimental outcomes.
Keywords: srdeční mitochondrie; Cell Line; signální transdukce; Cell Differentiation; mitochondrie; proteomika; hypoxie buňky; mitochondria; Signal Transduction; differentiation; Energy Metabolism; oxidativní fosforylace; Cell Proliferation; Myocytes, Cardiac; Mitochondria, Heart; Oxidative Phosphorylation; AC16; Mitochondrial Proteins; energetický metabolismus; Proteomics; Humans; hypoxia; metabolism; proliferace buněk; Mitochondria; buněčné linie; kardiomyocyty; buněčná diferenciace; Cell Hypoxia; mitochondriální proteiny; lidé